A low power low phase noise dual-band multiphase VCO - Xie, Juan (2013)
This paper presents a low-power low-phase noise multiphase VCO that operates in 2.5 GHz and 5.0 GHz frequency bands. The dual-band multiphase VCO uses the frequency doubling method to generate the higher band signals from the lower band signals, and it shows excellent phase noise performance compared to other dual-band multiphase VCOs presented in literature. The VCO has been implemented in 0.18 μm CMOS technology, and its frequency is tunable from 2.23 GHz to 2.68 GHz and from 4.46 GHz to 5.36 GHz. The measured phase difference between the I/Q signals is 90.0°/88.9° for the two frequency bands respectively. The phase noise figure-of-merits (FOMs) for the two frequency bands are −189.4 dB and −185.1 dB.